Design, Synthesis, and Versatile Processing of Indolo[3, 2‐b]indole‐Based π‐Conjugated Molecules for High‐Performance Organic Field‐Effect Transistors. (23rd March 2016) - Cho, Illhun; Park, Sang Kyu; Kang, Boseok; Chung, Jong Won; Kim, Jin Hong; Cho, Kilwon; Park, Soo Young
Abstract : A series of indolo[3, 2‐b]indole (IDID) derivatives comprising the core unit of N, N ‐dihexyl‐IDID with different aromatic and aliphatic substituents at 2‐ and 7‐position are designed and synthesized to construct high‐performance organic semiconductors by different processing routes. Structure‐property relationship of the derivatives is comprehensively studied in terms of their photophysical, electrochemical, structural, and electrical characteristics. IDID derivatives are either evaporated in vacuum or dissolved in common organic solvents to ensure applicalbility in different processing routes toward outstanding p‐type semiconductor films. Among others, the excellently soluble compound 4H4TIDID (with 2‐ and 7‐substituents of 5‐hexyl‐2, 2′‐bithiophene moiety, solubility >20 wt% in chloroform), shows the highest field‐effect hole mobility of 0.97 cm 2 V −1 s −1 in a device constructed by vacuum‐deposition and 0.18 cm 2 V −1 s −1 in device cosntructed by spin‐coating, respectively. The 2D grazing incidence X‐ray diffraction of 4H4TIDID films in both devices identically show the 2D molecular orientation favorable for the high transistor mobility. Abstract : A series of indolo[3, 2‐b]indole (IDID) derivatives are prepared to develop high‐performance organic semiconductors. Among others, films of compound 4H4TIDID possess a 2D ordered surface‐parallel orientation and respective devices exhibit hole mobilites of 0.97 cm 2 V −1 s −1 if formed by vacuum‐deposition, and 0.18 cm 2 V −1 s −1 if spin‐coated. The long‐axis parallel aliphatic units enhance solubility as well as charge transport property.